A Theoretical Study of Molecular Oxygen Chemisorption on N, B, or O Doped Carbon Edge Sites1. Issue 5 (15th September 2014) - Flyagina, I. S.; Hughes, K. J.; Pourkashanian, M.; Ingham, D. B.; Jones, Deborah; Jaouen, Frederic; Taillades‐Jacquin, Mélanie; Bucheli, Olivier
Abstract Molecular oxygen chemisorption on the edge sites of nitrogen, boron, or oxygen doped and non‐doped carbon has been studied by means of density functional theory in order to obtain a better insight into the first step of the oxygen reduction reaction (ORR) in fuel cells. The calculated chemisorption energies enabled us to evaluate thermodynamic favorability of the chemisorption products, and the activation energies revealed the most probable pathways of molecular oxygen chemisorption. It has been found that oxygen doped carbon edge sites can oxidize easily with disruption of the heterocyclic ring. Boron doped carbon edge sites can form stable B–O–C species and thus cause changes in the chemical structure of a boron doped carbon based catalyst. Molecular oxygen binding on carbon edge sites doped with graphitic nitrogen has been found to be improved compared to non‐doped, boron and pyridinic nitrogen doped carbon edge sites. Carbon edges doped with pyridinic nitrogen can serve as the sites for molecular oxygen chemisorption only in the presence of valence unsaturated carbon atoms. In general, the ORR both on non‐doped and heteroatom doped carbon edges initiates on the adjacent edge carbon atoms and is enhanced by the presence of graphitic nitrogen.